Prognostic significance of surgery‐induced sarcopenia in the survival of gastric cancer patients: a sex‐specific analysis. Issue 6 (17th September 2021) - Lee, Ja Kyung; Park, Young Suk; Lee, Kanghaeng; Youn, Sang Il; Won, Yongjoon; Min, Sa‐Hong; Ahn, Sang‐Hoon; Park, Do Joong; Kim, Hyung‐Ho
Abstract: Background: Preoperative sarcopenia is associated with a poor long‐term prognosis in patients with gastric cancer (GC). Most GC patients rapidly lose muscle mass after gastrectomy. This retrospective cohort study analysed the effect of postoperative muscle loss and surgery‐induced sarcopenia on the long‐term outcomes of patients with GC. Methods: Preoperative and postoperative 1 year abdominal computed tomography scans were available for 1801 GC patients who underwent curative gastrectomy between January 2009 and December 2013 at Seoul National University Bundang Hospital. The patients were categorized into normal, presarcopenia, and sarcopenia groups according to the skeletal muscle index (SMI) measured on computed tomography scans. Patients who were not sarcopenic prior to gastrectomy but became sarcopenic after surgery were defined as the surgery‐induced sarcopenia group. Results: There were 1227 men and 574 women included in the study. The mean age of the patients was 59.5 ± 12.3 years. Multivariable Cox‐regression analyses showed that preoperative SMI was not associated with overall survival (OS). However, postoperative sarcopenia was associated with significantly worse OS only in men [hazard ratio (HR), 1.75; 95% confidence interval (CI), 1.08–2.85]. SMI loss was an independent risk factor for OS in the entire cohort and in men (HR, 1.01; 95% CI, 1.00–1.02, for the entire cohort; HR, 1.02; 95% CI, 1.01–1.04, for men). The surgery‐induced sarcopenia group was associated with significantly higher mortality (HR, 1.84; 95% CI, 1.16–2.90, for the cohort; HR, 2.73; 95% CI, 1.54–4.82, for men), although SMI loss and surgery‐induced sarcopenia were not risk factors in women. Similar results were obtained for relapse‐free survival. Conclusions: Postoperative muscle mass loss and surgery‐induced sarcopenia are prognostic factors for survival in patients with GC. Impact of postoperative muscle mass loss and surgery‐induced sarcopenia on survival outcomes is dependent on the sex.